2015
DOI: 10.1007/s11920-015-0585-x
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Developmental and Risk Factor Research on Eating Disorders

Abstract: The Diagnostic and Statistical Manual of Mental Disorders (i.e., DSM-5) currently recognizes three primary eating disorders: anorexia nervosa, bulimia nervosa, and binge eating disorder. The origins of eating disorders are complex and remain poorly understood. However, emerging research highlights a dimensional approach to understanding the multifactorial etiology of eating disorders as a means to inform assessment, prevention, and treatment efforts. Guided by research published since 2011, this review summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 103 publications
(86 reference statements)
0
46
0
12
Order By: Relevance
“…Finally, psychological and psychosocial traits are universally recognized as key components in the etiology of eating disorders. Impaired psychosocial functioning, perfectionism, thin-ideal internalization, negative urgency, and sensitivity to reward and punishment are among the key risk factors that may predispose people to the onset of these illnesses [18,19]. …”
Section: Overview Of Eating Disorders: Classic Etiology Progressimentioning
confidence: 99%
“…Finally, psychological and psychosocial traits are universally recognized as key components in the etiology of eating disorders. Impaired psychosocial functioning, perfectionism, thin-ideal internalization, negative urgency, and sensitivity to reward and punishment are among the key risk factors that may predispose people to the onset of these illnesses [18,19]. …”
Section: Overview Of Eating Disorders: Classic Etiology Progressimentioning
confidence: 99%
“…This journal has played an important role in this development by publishing theoretical accounts of eating disorder risk (Pearson, Riley, Davis, & Smith, ) as well as this review, which identified risk factors that met clearly defined standards of empirical evidence. Other reviews (Bakalar, Shank, Vannucci, Radin, & Tanofsky‐Kraff, ) and theoretical accounts (Pearson, Wonderlich, & Smith, ) have also appeared recently in other outlets.…”
Section: Importance Of Disordered Eating In Child Mental Healthmentioning
confidence: 99%
“…Eating disorders are complex conditions in which genetics, personality, upbringing and culture can all play a role [1][2][3][4][5][6]. They are severe illnesses which can lead to significant somatic complications and death [7][8][9].…”
Section: Introductionmentioning
confidence: 99%